Black Box : Der Schwarzraum in der Kunst. - Beil, Ralf; Bronfen, Elisabeth; Busch, Bernd; Frohne, Ursula (Anna); Reust, Hans Rudolf; Schneemann, Peter J.; Zaunschirm, Thomas; Kunstmuseum Bern, Bern (Ostfildern-Ruit : Hatje Cantz Verlag, 2001)
Alÿs, Francis ; Boltanski, Christian ; Bourgeois, Louise ; Cardiff, Janet ; Eliasson, Olafur ; Gordon, Douglas ; Graham, Rodney ; Hill, Gary ; Miyajima, Tatsuo ; Oursler, Tony ; Smith/Stewart ; Steiner, Rudolf
autorenbiografien p. 165-166
biog. p. 153-158, literaturverzeichnis p. 159-163
Duits
Black Box : Der Schwarzraum in der Kunst, Kunstmuseum Bern, 15. Juni bis 9. September 2001
boek